Performance of early and long-duration rice (Oryza sativa) varieties in pure and mixed cropping systems under intermediate lowland condition - SHARMA, A R; GHOSH, A (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1994 and 1995 at Cuttack to study the yield performance of rice (Oryza sativa L.) varieties of early-duration (’Annada’ - dwarf, 105 days and ’Banaprabha’ - semi-tall, 95 days) and long-duration (’Gayatri’ - semi-dwarf, 170 days and ’CR 260-77’ - semi-tall, 170 days) in pure (sole crops) and mixed row stand (1:1 and 1:2 ratio) under intermediate lowland condition. The conventional long-duration varieties gave more than double the grain yield obtained from the early varieties in pureÂ stand. The tall varieties of both maturity groups(’Banaprabha’ and ’CR 260-77’) performed better than dwarfvarieties (’Annada’ and ’Gayatri’) in pure as well as mixed stand. The total grain yield in mixed stand of’Banaprabha’ with long-duration varieties was significantly higher (16.1-16.9%) than pure crop of late variety alone. The increase in yield in mixed stand was due to long-duration varieties which gave 82.6-85.3% of their yield in pure stand due to higher panicle weight following wider row spacing after the harvest of early varieties in September. Land-equivalent ratio in mixed cropping of ’Gayatri’ or ’CR 260-77’ with ’Bnnaprabha’ was 1.40-1.52 but only 1.14-1.21 with’ Annada’. An yield advantage of about 0.5 tonne/ha was achieved in the mixed cropping system which could be beneficial for avoiding risk ancl achieving sustainable production in the fragile lowland ecosystems.